2019
DOI: 10.24191/smrj.v16i2.7060
|View full text |Cite
|
Sign up to set email alerts
|

Attitude in Learning Physics among Form Four Students

Abstract: Physics is considered as the most challenging area of learning within the field of science, and it usually magnetises fewer students compared to other science related subjects from secondary school to university. Generally, students tend to have a negative attitude towards physics presumably because they lack interest in the subject and the syllabus itself. This research is carried out to study the learning attitude in physics and challenges towards learning force and motion among Form Four students in Klang. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…More recently, Balfakih's conclusions were supported by Ibrahim et al (2019) whose arguments were quoted above and who contend that, in the UAE, negative attitudes towards physics are contributing directly to students' "dislike" of physics.…”
Section: Research Problemmentioning
confidence: 93%
See 2 more Smart Citations
“…More recently, Balfakih's conclusions were supported by Ibrahim et al (2019) whose arguments were quoted above and who contend that, in the UAE, negative attitudes towards physics are contributing directly to students' "dislike" of physics.…”
Section: Research Problemmentioning
confidence: 93%
“…It has been acknowledged so far the students are not doing well in physics due to traditional instructional methods as stated by Balfakih (2010) and Ibrahim, Zakiang and Damio (2019) whose results revealed that in physics, students are not where they should be and do not meet the expectations.…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Mata pelajaran fizik menerangkan konsep yang tidak dapat dilihat melalui pemerhatian dengan mata kasar mengenai perkara yang berlaku dalam kehidupan harian (Mufit et al, 2020;Saprudin et al, 2019) seperti graf yang digunakan sebagai perwakilan bagi menggambarkan pergerakan sesuatu jasad. Hal ini menyebabkan pelajar mengalami kesukaran untuk menguasai mata pelajaran fizik (Mazlena Murshed, 2020;Norbaizura Nordin & Rozidawati Awang, 2021;Norezan Ibrahim et al, 2019). Salah satu kesukaran yang dihadapi oleh pelajar adalah mentafsir graf yang mewakili maklumat yang kompleks dalam mata pelajaran fizik (Amin et al, 2020;Antwi et al, 2018;Norbaizura Nordin, 2019;Norbaizura Nordin & Rozidawati Awang, 2021;Phage, 2018).…”
Section: Pendahuluanunclassified
“…The 2019 MCE examination data reveals a consistent run over several years in terms of percentage of students (Ministry of Education, 2019) who have achieved excellent results in physics paper. Such level of achievement may be explained by the students' lack of interest towards learning physics (Ibrahim et al, 2019). Additionally, students ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ usually describe physics as a complex and dull subject (Archer et al, 2020).…”
Section: The Current Status Of Pe In Malaysiamentioning
confidence: 99%